The Barriers and Challenges of Corporate Governance in Jordanian Companies: An Evaluation of the Reality of Corporate Governance in Jordan - Aleqedart, Houda Qasim (International Journal of Business Studies, 2020)
This paper aimed to identify and analyze the obstacles and challenges facing the implementation of corporate governance in Jordanian companies by using collecting data from books, periodicals, previous research and interviews to access answers to questions of research. The qualitative research method and interviews have been conducted to obtain different answers to the research questions. The paper compared the data collected from articles and interviews in order to examine the extent of compliance of Jordanian legislation and companies with the principles of corporate governance. The paper concluded that there is a unanimous agreement that corporate governance is a critical factor in corporate success. However, there are restrictions and barriers that hinder the progress of good practices of corporate governance. Furthermore, there is no general implementation of the concept in its entirety, this may be because the rules of corporate governance are indicative and non-binding as they aim to raise the level of management in companies and protect the rights of shareholders. Therefore, it is necessary to recommend here to adopt this issue in future research by studying how to overcome these barriers, which may positively affect companies.